2011
DOI: 10.2298/sgs1103139k
|View full text |Cite
|
Sign up to set email alerts
|

Radiological assessment of the quality of root canal fillings in teeth endodontically treated at students’ practical sessions

Abstract: Introduction The main goal of obturation is prevention of reinfection of the root canal system and consequently appearance of periapical lesion. Epidemiological studies have confirmed high prevalence of periapical lesions in endodontically treated teeth with inadequate root canal fillings. The aim of this study was to assess the quality of root canal fillings in teeth treated at students' practical sessions. Iatrogenic errors during endodontic interventions were also assessed. Methods Two hundred dental record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…In this study, similar to Kulic et al (2011), multi root teeth which had error during treatment, even in one canals, was considered as unacceptable treatment. Unal et al (2011) reported highest prevalence of acceptable treatment in anterior teeth was 90.1% and the least prevalence was reported in 46.6% molars.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In this study, similar to Kulic et al (2011), multi root teeth which had error during treatment, even in one canals, was considered as unacceptable treatment. Unal et al (2011) reported highest prevalence of acceptable treatment in anterior teeth was 90.1% and the least prevalence was reported in 46.6% molars.…”
Section: Resultsmentioning
confidence: 96%
“…Kelbauskas et al (2009) reported that 5.42% had overfi lling which was compatible with this study. Kulic et al (2011) reported3.3% overfi lling which this low prevalence can be due to less numbers of their samples (306 canal). Er et al (2006) reported 13% overfi lling cases and Khabbaz et al reported 22.6% overfi lling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) Therefore, in order to evaluate the endodontic status, numerous studies have focused on the prevalence and quality of root canal treatment. (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Several reports indicated that the prevalence of root canal treatment varies from 2.1% to 23.4% (15)(16)(17)(18)(19)(20)(21) and increases with age (22)(23) and the prevalence of apical periodontitis varies from 1.6% to 27.0% (1,4,5,7-10, [15][16][17][18]20,[22][23][24][25][26] Radiology is especially important for diagnosis in the detection of periapical lesions, and to assess treatment success including post-treatment healing. (1,4,5,7,9) The interpretation of radiographs is the only method that can be used to evaluate periapical health in an epidemiologic study.…”
Section: Introductionmentioning
confidence: 99%